Peril at the exposition [large type] - March, Nev, 1967- (March, Nev, 1967- Captain Jim and Lady Diana mysteries, 2025)
"1893: Newlyweds Captain Jim Agnihotri and Diana Framji are settling into their new home in Boston, Massachusetts, having fled the strict social rules of British Bombay. It's a different life than what they left behind, but theirs is no ordinary marriage: Jim, now a detective at the Dupree Agency, is teaching Diana the art of deduction he's learned from his idol, Sherlock Holmes. Everyone is talking about the preparations for the World's Fair in Chicago: the grandeur, the speculation, the trickery. Captain Jim will experience it first-hand: he's being sent to Chicago to investigate the murder of a man named Thomas Grewe. As Jim probes the underbelly of Chicago's docks, warehouses, and taverns, he discovers deep social unrest and some deadly ambitions. When Jim goes missing, young Diana must venture to Chicago's treacherous streets to learn what happened. But who can she trust, when a single misstep could mean disaster?" --